Pengembangan Mainan Rocking Toy untuk Anak Usia 3-5 Tahun dengan Menerapkan Tema Tron Guna Meningkatkan Imajinasi Anak - R, Indra Gunara; Luvia, Luvia (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Toys are one of the child's motor supporters when they enter the age of 3-5 years when the child is experiencing brain development reaches 80% and occurs once in a lifetime. Appropriate coaching is strongly recommended for good emotional, mental, social, intellectual, moral and physical development. Therefore it takes a suitable toy for children's growth that not only as entertainment alone but also can help stimulate his physical motor. Rocking toy or famous for toy piggyback is a toy that can help the motor development of children and also imagination. And along with the development of the child's imagination time has begun to grow as well, by adjusting what the child likes from spectacle, comic, or super hero characters in story books.